Study of duration and efficacy of chloroprocaine for spinal anesthesia in infraumbilical surgeries - Memon, Nazima; Pathak, R.G.; Pradeep, Meenakshi S. (Asian Journal of Medical Sciences, 2021)
Background: Spinal anesthesia is a reliable and safe technique for infraumbilical surgeries. Nevertheless, some of its characteristics may limit its use for day care surgery. Use of long-acting anesthetic drugs like bupivacaine in spinal anesthesia may lead to side effects such as delayed ambulation and risk of urinary retention. Chloroprocaine is an amino-ester local anesthetic with a very short half-life now being extensively evaluated in volunteer studies and clinical practice with a favorable safety profile and efficacy, suggesting that it may be a suitable alternative to long-acting local anesthetics like bupivacaine in day care surgeries. Aims and Objective: This study aims at evaluating the duration and efficacy of chloroprocaine in spinal anesthesia for infraumbilical surgeries. The primary outcome of the study was to evaluate the duration and efficacy of chloroprocaine 1% in spinal anesthesia for infraumbilical surgeries and the secondary outcome was to find out the incidence of adverse effects if any. Materials and Methods: In this randomized single-blinded clinical evaluation, after institutional ethical committee approval, 30 adult patients (18–70 years, ASA physical Status I-III, BMI < 36 kg/m2) scheduled for infraumbilical surgeries received chloroprocaine 40 mg intrathecally. Patients were evaluated for onset and regression of sensory and motor blockade, peak level of sensory blockade, and time of ambulation postoperatively. Results: The average duration of the surgeries was 46.87±15.24 min. Anesthesia was sufficient for the planned surgery. Only three patients required sedation intraoperatively. The median peak sensory block height was T8. The mean time for peak height sensory block was 6.6±1.673 min and complete motor block was 2±1.05 min. Mean time for complete sensory block regression was 95.37±20.79 min and complete motor block regression was 81.43±20.33 min. Four patients required inj. atropine following bradycardia and three patients required vasopressors following hypotension. Conclusion: Spinal anesthesia with chloroprocaine provides reliable sensory and motor block for short duration infraumbilical surgeries with fewer intraoperative and post-operative complications.